Risk rationing and agricultural credit demand in Kyrgyzstan: Evidence from life in Kyrgyzstan survey - Ishkinina, Salia; Sultakeev, Kadyrbek (Asian Journal of Agriculture and Rural Development, 2026)
This study investigates the nature, causes, and behavioral effects of agricultural credit limits among rural households in Kyrgyzstan using nationally representative data from the 2019 Life in Kyrgyzstan (LiK) Survey. Despite recent growth in the domestic financial sector, formal credit remains difficult to obtain, especially for smallholder farmers. The analysis employs a direct elicitation methodology that categorizes families into four groups: unconstrained, quantity-rationed, price-rationed, and risk-rationed, to better capture both supply-side and demand-side restrictions. To identify the key variables associated with each type of constraint, a multinomial logit model is utilized. The findings reveal that risk rationing is the most prevalent form of credit exclusion, affecting approximately one-third of rural households. This indicates that borrowing decisions are more influenced by households' perceptions of risks, such as concerns about repayment, the threat of losing collateral, and limited trust in financial institutions, rather than merely the availability of credit. Additionally, the location of households significantly impacts the likelihood of quantity rationing. Exposure to adverse shocks notably increases the probability of credit limits among rural households, highlighting the importance of external factors in credit access issues.